O abate de frangos pelo método Kosher: definições, conjuntura de mercado e perspectivas de estudo - Izidoro, Thiago Braga [UNESP] (2012)
Kosher food is understood as being the appropriate one for a Jew, ensuring this way their physical and spiritual health. It follows a series of food standards contained in the Halakha, which is a set of laws governing the proper moral conduct of the Jewish culture. Currently the market for Kosher food moves about 200 billion dollars in the USA, with consumers not only among Jews, but also among Muslims, vegetarians and people who associate such products with a more rigorous quality control. To be considered Kosher, a product has to go through some changes in its production flowchart, being the slaughter of chickens one of the most modified compared to the conventional method. Given the importance of the subject, new lines of research have emerged in order to determinate how the insertion or the alteration in the flowchart steps practiced in the Kosher food industry influence the food overall quality and safety.